Efeito da modulação laser de baixa intensidade na regeneração de tendões de ratos jovens e adultos - Taciro, Charles (Universidade Federal de São Carlos, 2011)
Aging is an important factor related to the predisposition to tendon degeneration, pathological and delayed tissue repair. Several physical therapy modalities are used to promote acceleration and improvement of tendon healing, among them the low-level laser therapy (LLLT), but the real effects of this therapy associated with the development and aging effects are not yet known. The present study evaluated the effects of LLLT, applied on the calcanear tendon repair after total tenotomy on calcaneal tendon of rats in two different ages. Young rats (4 weeks old, n = 56, body mass = 111.3 8.3g), randomly divided into 4 subgroups containing 14 animals: J3J (3J/cm2, 8.5mJ/session, 5.0seg/session), J10J (10J/cm2, 28.3mJ/session, 15seg/session), placebo - JPL (0J/cm2), control - JCL (no treatment) and an adult group (27 weeks old, n = 56, body mass = 385.4 34.3g), randomly divided into 4 subgroups: A3J (3J/cm2, 8.5mJ/session, 5.0seg/session), A10J (10J/cm2, 28.3mJ/session, 15seg/session), placebo - APL (0J/cm2) control - ACL (no treatment). LLLT (685nm, 5.4W/cm2) was applied in 12 sessions, once a day, at a single point on the injury site. On the 13th postoperative day, the animals were euthanized and their tendons were removed. The tendon collagen organization was analyzed by polarization microscopy. The metalloproteinases activity (MMP-2 and MMP-1) was analyzed by zymography, nitric oxide (NO) production was analyzed by Griess method and the concentration of interleukin-1beta (IL-1 ) and interleukin-10 (IL- 10) by ELISA method. The data analysis showed significant (p <0.05) tissue response to LLLT, both age-dependent and dose-dependent, and the results showed major changes to the adult group at 3J/cm2 when compared to other subgroups in the evaluation of IL-1, IL-10 and birefringence, which we can see a potentially inhibitory and stimulatory window.
Keywords: Fisioterapia; Laserterapia; Envelhecimento; Tendão de aquiles; Tendão; Laser therapy; Aging; Tendon; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL